High-performance composite capacitor base film and preparation method thereof

By compounding PEN and PET in the capacitor base film and constructing a three-dimensional network structure of composite reinforced modified particles, the problem of withstand voltage and life of the capacitor base film under high-frequency or high-pulse conditions is solved, and higher mechanical performance is achieved. Strength, heat resistance and oxidation resistance.

CN118772459BActive Publication Date: 2025-01-21扬州博恒新能源材料科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410979561.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-01-21
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

The existing capacitor base films are prone to problems such as increasing self-healing point, reducing voltage withstandness, and shortening of life under high frequency or high pulse conditions. Moreover, carbon nanotubes are difficult to disperse in the polyester base film, and the improvement of oxidation resistance is limited.

Method used

PEN and PET are used as polyester masterbatch, and composite reinforced modified particles are constructed through materials such as acid-modified carbon nanotubes, nano-SiO2 and nano-alumina to form a three-dimensional network structure to improve the mechanical strength and heat resistance of the base film. performance and antioxidant properties.

Benefits of technology

It significantly improves the mechanical strength, heat resistance and oxidation resistance of the capacitor base film, extends its service life, and improves stability under high-frequency or high-pulse conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118772459B_ABST
    Figure CN118772459B_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance composite capacitor base film and a preparation method thereof, the method comprising the following steps: step 1, mixing polyester masterbatch and composite reinforced modified particles to obtain an extrusion masterbatch; step 2, melt extrusion, cooling, and casting; step 3, preheating the cast sheet and performing longitudinal stretching; step 4, preheating, performing transverse stretching; step 5, shaping treatment, and finally cooling, winding, and trimming to obtain a high-performance composite capacitor base film. The invention adopts PEN and PET compound as polyester masterbatch, which can improve the mechanical strength and heat resistance of the base film. The composite reinforced modified particles in the invention adopt acid-modified carbon nanotubes and nano-SiO2 as the main reinforcing fillers, and compound nano-alumina and reduced carbon dots to form a special three-dimensional network structure, which can comprehensively improve the mechanical strength, heat resistance and oxidation resistance of the base film, improve the application effect of the base film, and extend its service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of capacitor base films, and in particular to a high-performance composite capacitor base film and a preparation method thereof. Background Art

[0002] Capacitor film is the core material of film capacitors. As one of the three major passive components, capacitors are widely used in various electronic products. Among them, film capacitors benefit from their high voltage resistance, good temperature characteristics, and long life. They have obvious advantages and broad prospects in new energy fields such as new energy vehicles, photovoltaics and wind power generation. Film capacitors are basic electronic components with the advantages of high insulation impedance, low dielectric loss, high dielectric strength, long service life, and excellent frequency characteristics. They are widely used in many industries such as home appliances, communications, power grids, rail transit, industrial control, and new energy.

[0003] When capacitors are used under high frequency or high pulse conditions, the pulse current passing through the capacitor will cause the capacitor to heat up and increase its temperature, leading to problems such as increased self-healing point, reduced withstand voltage, and shortened life. At present, the temperature resistance of most capacitor polyester-based films is average, which in turn affects the service life of the capacitor. Therefore, it is urgent to improve the heat resistance and mechanical strength of the capacitor film and extend its service life.

[0004] Carbon nanotubes have excellent mechanical strength and heat resistance and have been used in the preparation of capacitor base films, such as the multilayer composite BOPE capacitor film and its preparation method disclosed in Chinese patent CN114103348B, and the literature "Wang Lu. Assembly and capacitance performance of all-solid-state flexible manganese dioxide nanowire bundle / single-walled carbon nanotube composite film capacitor [D]. Shaanxi Normal University, 2017." However, carbon nanotubes have the defect of being difficult to disperse in polyester base films, and their effect on improving the antioxidant properties of base films is limited.

[0005] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a high-performance composite capacitor base film and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high-performance composite capacitor base film, comprising the following steps:

[0008] Step 1: mixing polyester masterbatch and composite reinforced modified particles to obtain extrusion masterbatch;

[0009] Wherein, the polyester masterbatch is a mixture of PET masterbatch and PEN masterbatch;

[0010] Step 2, adding the extrusion masterbatch into the extruder for melting and extrusion, cooling, and casting;

[0011] Step 3, preheating the cast sheet, and then longitudinally stretching it on a longitudinal stretching machine to obtain a longitudinally stretched sheet;

[0012] Step 4, preheating the longitudinally stretched sheet, and then performing transverse stretching on a transverse stretching machine to obtain a biaxially stretched sheet;

[0013] Step 5: The biaxially stretched sheet is subjected to shaping treatment, and finally cooled, rolled up, and trimmed to obtain the high-performance composite capacitor base film.

[0014] Preferably, the method for preparing the high-performance composite capacitor base film comprises the following steps:

[0015] Step 1, mixing the polyester masterbatch and the composite reinforced modified particles at 40-70° C. for 30 minutes to obtain an extrusion masterbatch;

[0016] The polyester masterbatch is a mixture of PET masterbatch and PEN masterbatch, and the mass ratio of PET masterbatch to PEN masterbatch is 5:1-2.5:1;

[0017] The addition amount of composite reinforced modified particles is 1.8-4.5% of the polyester masterbatch mass;

[0018] Step 2, adding the extrusion masterbatch into the extruder, melting and extruding at 250-270°C, cooling, and casting at 25-35°C;

[0019] Step 3, preheating the cast sheet at 60-70° C., and then longitudinally stretching it at 70-80° C. on a longitudinal stretching machine to obtain a longitudinally stretched sheet, with a longitudinal stretching ratio of 3-3.5 times;

[0020] Step 4, preheating the longitudinally stretched sheet at 85-95°C, and then transversely stretching it at 110-125°C on a transverse stretching machine to obtain a biaxially stretched sheet with a transverse stretching ratio of 2.5-3.5 times;

[0021] Step 5: The biaxially stretched sheet is subjected to a shaping treatment at 75-95° C., and finally cooled, rolled up, and trimmed to obtain the high-performance composite capacitor base film.

[0022] Preferably, the method for preparing the high-performance composite capacitor base film comprises the following steps:

[0023] Step 1: Mix the polyester masterbatch and the composite reinforced modified particles at 55° C. for 30 minutes to obtain an extrusion masterbatch; wherein:

[0024] The polyester masterbatch is a mixture of PET masterbatch and PEN masterbatch, and the addition amount of the composite reinforced modified particles is 3.2% of the mass of the polyester masterbatch;

[0025] Step 2, adding the extrusion masterbatch into the extruder, melting and extruding at 265°C, cooling, and casting at 30°C;

[0026] Step 3, preheating the cast sheet at 70°C, and then longitudinally stretching it at 120°C on a longitudinal stretching machine to obtain a longitudinally stretched sheet, with a longitudinal stretching ratio of 3.5 times;

[0027] Step 4, preheating the longitudinally stretched sheet at 95°C, and then transversely stretching it at 115°C on a transverse stretching machine to obtain a biaxially stretched sheet, with a transverse stretching ratio of 3 times;

[0028] Step 5: The biaxially stretched sheet is subjected to a shaping treatment at 90° C., and finally cooled, rolled up, and trimmed to obtain the high-performance composite capacitor base film.

[0029] Preferably, in the polyester masterbatch, the mass ratio of PET masterbatch:PEN masterbatch is 3:1.

[0030] Preferably, the composite reinforced modified particles are prepared by the following method:

[0031] S1, preparing acid-modified carbon nanotubes;

[0032] S2. Preparation of modified particle intermediates:

[0033] S2-1, adding acid-modified carbon nanotubes, nano-SiO2, and aluminum nitrate into a mixed solution of deionized water and ethanol, and performing ultrasonic dispersion;

[0034] S2-2, adding glucose, tert-butylhydroquinone, ethylenediamine and salicylic acid to the mixture obtained in step S2-1, and dispersing by ultrasonication to obtain a precursor solution;

[0035] S2-3, transferring the precursor solution to a reactor, heating the reaction, cooling to room temperature after the reaction, filtering, washing the solid, and then vacuum drying to obtain a modified particle intermediate;

[0036] S3, modifying the surface of the modified particle intermediate with phenylacetic acid to obtain the composite enhanced modified particle.

[0037] Preferably, step S1 specifically comprises:

[0038] Take 2.5-10g of multi-walled carbon nanotubes and add them to a mixed solution of 200-500mL of 98wt% concentrated nitric acid and 50-200mL of 67wt% concentrated nitric acid, reflux at 85-100°C for 4-8h, cool, filter, wash with deionized water until neutral, and vacuum dry at 100-120°C for 2-8h to obtain acid-modified carbon nanotubes.

[0039] Preferably, step S2 specifically comprises:

[0040] S2-1, add 0.75-3g of acid-modified carbon nanotubes, 1-4g of nano-SiO2, and 0.426-1.7g of aluminum nitrate into a mixed solution consisting of 150-600mL of deionized water and 100-400mL of ethanol, and disperse by ultrasonic for 15-60min;

[0041] S2-2, adding 360-1440 mg of glucose, 166-664 mg of tert-butylhydroquinone, 92-368 mg of ethylenediamine, and 345-1380 mg of salicylic acid to the mixture obtained in step S2-1, and ultrasonically dispersing for 30-90 min to obtain a precursor solution;

[0042] S2-3. Transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 175-200°C for 6-12 hours, cool to room temperature after the reaction, filter, wash the solid with deionized water and ethanol in turn, and then vacuum dry at 80-95°C for 6-24 hours to obtain a modified particle intermediate.

[0043] Preferably, step S3 specifically comprises:

[0044] 0.5-2 g of the modified particle intermediate and 1-4 mmol of phenylacetic acid are added to 25-100 mL of ethanol, refluxed at 50-65° C. for 8-24 h, filtered, the solid product is washed with ethanol, and then dried at 60-80° C. for 6-20 h to obtain the composite reinforced modified particles.

[0045] Preferably, the composite reinforced modified particles are prepared by the following method:

[0046] S1. Preparation of acid-modified carbon nanotubes:

[0047] 5 g of multi-walled carbon nanotubes were added to a mixed solution of 300 mL of 98 wt% concentrated nitric acid and 100 mL of 67 wt% concentrated nitric acid, refluxed at 90° C. for 6 h, cooled, filtered, washed with deionized water until neutral, and vacuum dried at 110° C. for 4 h to obtain acid-modified carbon nanotubes;

[0048] S2. Preparation of modified particle intermediates:

[0049] S2-1, 1.5 g of acid-modified carbon nanotubes, 2 g of nano-SiO2, and 0.852 g of aluminum nitrate were added to a mixed solution consisting of 300 mL of deionized water and 200 mL of ethanol, and ultrasonically dispersed for 30 min;

[0050] S2-2, adding 720 mg of glucose, 332 mg of tert-butylhydroquinone, 184 mg of ethylenediamine, and 690 mg of salicylic acid to the mixture obtained in step S2-1, and ultrasonically dispersing for 45 minutes to obtain a precursor solution;

[0051] S2-3, transferring the precursor solution to a polytetrafluoroethylene-lined reactor, reacting at 185°C for 10 hours, cooling to room temperature after the reaction, filtering, washing the solid with deionized water and ethanol in sequence, and then vacuum drying at 90°C for 12 hours to obtain a modified particle intermediate;

[0052] S3, taking 1 g of the modified particle intermediate and 2 mmol of phenylacetic acid, adding them into 50 mL of ethanol, refluxing at 58° C. for 16 h, filtering, washing the solid product with ethanol, and then drying at 70° C. for 12 h to obtain the composite reinforced modified particles.

[0053] The present invention also provides a high-performance composite capacitor base film, which is prepared by the method as described above.

[0054] The beneficial effects of the present invention are:

[0055] The invention provides a high-performance composite capacitor base film and a preparation method thereof. The invention adopts PEN and PET compounded as polyester masterbatch, which can improve the mechanical strength and heat resistance of the base film; wherein, the benzene ring in PET is replaced by a naphthalene ring in the PEN (polyethylene naphthalate) molecule, and the naphthalene ring has a more stable structure than the benzene ring, the molecular chain has greater rigidity, and the structure is more planar, so the mechanical and chemical properties are better.

[0056] The present invention adopts composite reinforced modified particles as additives to improve the comprehensive performance of the base film. The composite reinforced modified particles use acid-modified carbon nanotubes and nano-SiO2 as the main reinforcing fillers, and are compounded with nano-alumina and reduced carbon dots to form a special three-dimensional network structure, which can comprehensively improve the mechanical strength, heat resistance and oxidation resistance of the base film, improve the application effect of the base film, and extend its service life;

[0057] In the composite reinforced modified particle system of the present invention, aluminum ions play multiple bridging roles during the preparation process, and the nano-alumina finally formed can serve as a connecting node of the network structure, thereby improving the physical strength of the network structure. At the same time, the nano-alumina also has the following functions in the base film system: providing high temperature resistance and chemical resistance, improving basic mechanical strength, and improving voltage resistance;

[0058] In the composite enhanced modified particle system of the present invention, the carbon nanotubes can improve the tensile strength, breakdown strength and thermal stability of the base film, and the nano-SiO2 has a high dielectric constant and excellent chemical stability, which can improve the strength and stability of the film;

[0059] In the composite reinforced modified particle system of the present invention, the carbon dots synthesized in situ on the three-dimensional network structure inherit the excellent reducibility of tert-butylhydroquinone and show good antioxidant properties, thereby enhancing the antioxidant capacity of the base film and extending its service life. On the other hand, the benzene ring structure introduced by tert-butylhydroquinone and salicylic acid in the carbon dots can form CH-π interactions with PET and PEN molecular chains, thereby accelerating nucleation and crystallization and improving mechanical properties;

[0060] In the composite reinforced modified particle system of the present invention, by constructing a three-dimensional network structure and modifying phenylacetic acid, the dispersion performance of carbon nanotubes and nano-SiO2 can be greatly improved, and their uniform dispersion in the base film system can be promoted, so as to give full play to their reinforcing effect, thereby overcoming the application difficulties of carbon nanotubes and nano-SiO2 at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 The antioxidant performance test results of the composite reinforced modified particles prepared in Example 1;

[0062] Figure 2 This is the infrared absorption spectrum of the composite reinforced modified particles prepared in Example 1. DETAILED DESCRIPTION

[0063] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0064] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0065] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0066] The present invention provides a method for preparing a high-performance composite capacitor base film, comprising the following steps:

[0067] Step 1, mixing the polyester masterbatch and the composite reinforced modified particles at 40-70° C. for 30 minutes to obtain an extrusion masterbatch;

[0068] The polyester masterbatch is a mixture of PET masterbatch and PEN masterbatch, and the mass ratio of PET masterbatch to PEN masterbatch is 5:1-2.5:1;

[0069] The addition amount of composite reinforced modified particles is 1.8-4.5% of the polyester masterbatch mass;

[0070] Step 2, adding the extrusion masterbatch into the extruder, melting and extruding at 250-270°C, cooling, and casting at 25-35°C;

[0071] Step 3, preheating the cast sheet at 60-70° C., and then longitudinally stretching it at 70-80° C. on a longitudinal stretching machine to obtain a longitudinally stretched sheet, with a longitudinal stretching ratio of 3-3.5 times;

[0072] Step 4, preheating the longitudinally stretched sheet at 85-95°C, and then transversely stretching it at 110-125°C on a transverse stretching machine to obtain a biaxially stretched sheet with a transverse stretching ratio of 2.5-3.5 times;

[0073] Step 5: The biaxially stretched sheet is subjected to a shaping treatment at 75-95° C., and finally cooled, rolled up, and trimmed to obtain the high-performance composite capacitor base film.

[0074] In a preferred embodiment, the composite reinforced modified particles are prepared by the following method:

[0075] S1. Preparation of acid-modified carbon nanotubes:

[0076] Take 2.5-10g of multi-walled carbon nanotubes and add them to a mixed solution of 200-500mL of 98wt% concentrated nitric acid and 50-200mL of 67wt% concentrated nitric acid, reflux at 85-100°C for 4-8h, cool, filter, wash with deionized water until neutral, and vacuum dry at 100-120°C for 2-8h to obtain acid-modified carbon nanotubes.

[0077] S2. Preparation of modified particle intermediates:

[0078] S2-1, add 0.75-3g of acid-modified carbon nanotubes, 1-4g of nano-SiO2, and 0.426-1.7g of aluminum nitrate into a mixed solution consisting of 150-600mL of deionized water and 100-400mL of ethanol, and disperse by ultrasonic for 15-60min;

[0079] S2-2, adding 360-1440 mg of glucose, 166-664 mg of tert-butylhydroquinone, 92-368 mg of ethylenediamine, and 345-1380 mg of salicylic acid to the mixture obtained in step S2-1, and ultrasonically dispersing for 30-90 min to obtain a precursor solution;

[0080] S2-3. Transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 175-200°C for 6-12 hours, cool to room temperature after the reaction, filter, wash the solid with deionized water and ethanol in turn, and then vacuum dry at 80-95°C for 6-24 hours to obtain a modified particle intermediate.

[0081] S3. Modify the surface of the modified particle intermediate with phenylacetic acid to obtain composite enhanced modified particles.

[0082] Take 0.5-2g of the modified particle intermediate and 1-4mmol of phenylacetic acid and add them to 25-100mL of ethanol, reflux at 50-65°C for 8-24h, filter, wash the solid product with ethanol, and then dry at 60-80°C for 6-20h to obtain composite reinforced modified particles.

[0083] In the PEN (polyethylene naphthalate) molecule, the naphthalene ring replaces the benzene ring in PET. The naphthalene ring has a more stable structure than the benzene ring, the molecular chain is more rigid, and the structure is more planar, so the mechanical and chemical properties are better. In the present invention, PEN and PET are compounded as a masterbatch to improve the mechanical strength and heat resistance of the base film.

[0084] The composite reinforced modified particles in the present invention use acid-modified carbon nanotubes and nano-SiO2 as the main reinforcing fillers, and are compounded with nano-alumina and reduced carbon dots to form a special three-dimensional network structure, which can comprehensively improve the mechanical strength, heat resistance and oxidation resistance of the base film, improve the application effect of the base film, and extend its service life. The main mechanism of the composite reinforced modified particles is explained below in conjunction with a specific preparation method to facilitate understanding of the present invention.

[0085] 1. The present invention first introduces abundant -COOH functional groups into the multi-walled carbon nanotubes through strong acid oxidation modification, which can help improve the dispersibility of the multi-walled carbon nanotubes;

[0086] 2. Then, glucose, tert-butylhydroquinone, ethylenediamine, and salicylic acid were used as carbon dot raw materials, acid-modified carbon nanotubes and nano-SiO2 were used as carriers, and aluminum ions were used as crosslinkers. A modified particle intermediate with a three-dimensional network structure was synthesized by a one-pot hydrothermal method;

[0087] In this process, acid-modified carbon nanotubes, nano-SiO2 and aluminum nitrate are first mixed, and the aluminum ions are combined with the -COOH functional groups on the acid-modified carbon nanotubes and the silanol groups of the nano-SiO2 through coordination or electrostatic adsorption, so that the nano-SiO2 can be attached to the acid-modified carbon nanotubes, and through the mutual combination of the two, a three-dimensional network structure with aluminum ions as connecting nodes can eventually be formed; after mixing with the carbon dot raw materials, the aluminum ions again act as cross-linkers to attract the attachment of precursors such as salicylic acid and glucose, and finally, through high-temperature hydrothermal reaction, carbon dots are in situ synthesized on the three-dimensional network structure formed by the acid-modified carbon nanotubes and nano-SiO2, and the aluminum ions form nano-alumina as a firm network connecting node.

[0088] 3. Finally, phenylacetic acid is used to modify the modified particle intermediate. The aluminum ions formed on the surface of nano-alumina can achieve a large number of connections of phenylacetic acid on the surface. The modification of phenylacetic acid can greatly improve the dispersibility of the composite reinforced modified particles in the PET and PEN systems and avoid their agglomeration.

[0089] In the composite reinforced modified particle system of the present invention, aluminum ions play multiple bridging roles in the preparation process, and the nano-alumina finally formed can serve as a connecting node of the network structure, thereby improving the physical strength of the network structure. At the same time, the nano-alumina also has the following functions in the base film system: providing high temperature resistance and chemical resistance, improving basic mechanical strength, and improving voltage resistance.

[0090] In the composite reinforced modified particle system of the present invention, the carbon nanotubes can improve the tensile strength, breakdown strength and thermal stability of the base film, and the nano-SiO2 has a high dielectric constant and excellent chemical stability, and can improve the strength and stability of the film.

[0091] In the composite reinforced modified particle system of the present invention, the carbon dots synthesized in situ on the three-dimensional network structure inherit the excellent reducibility of tert-butylhydroquinone and show good antioxidant properties, thereby enhancing the antioxidant capacity of the base film and extending its service life. On the other hand, the benzene ring structure introduced by tert-butylhydroquinone and salicylic acid in the carbon dots can form CH-π interactions with PET and PEN molecular chains, thereby accelerating nucleation and crystallization and improving mechanical properties.

[0092] In the present invention, the thermal oxidation resistance of the base film is significantly improved, which is mainly attributed to the following two aspects: (1) the addition of carbon nanotubes and SiO2 can improve the thermal stability and chemical stability; the formation of aluminum oxide can improve the heat resistance; (2) the reducing property imparted by the carbon dots can eliminate oxygen free radicals and enhance the antioxidant capacity.

[0093] In the composite reinforced modified particle system of the present invention, by constructing a three-dimensional network structure and modifying phenylacetic acid, the dispersion performance of carbon nanotubes and nano-SiO2 can be greatly improved, and their uniform dispersion in the base film system can be promoted, so as to give full play to their reinforcing effect, thereby overcoming the application difficulties of carbon nanotubes and nano-SiO2 at the same time.

[0094] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0095] Main product sources:

[0096] PET (polyethylene terephthalate), DuPont, USA, brand number RE5329;

[0097] PEN (polyethylene naphthalate), Teijin, Japan, brand TN8065S;

[0098] Multi-walled carbon nanotubes, inner diameter: 20-50 nm, length: 1-10 μm, Suzhou Beike Nanotechnology Co., Ltd.;

[0099] Nano-SiO2, Suzhou Beike Nano-Tech Co., Ltd., average particle size 30nm, specific surface area 200m 2 / g.

[0100] Example 1

[0101] A high-performance composite capacitor base film, the preparation method of which comprises the following steps:

[0102] Step 1: Mix the polyester masterbatch and the composite reinforced modified particles at 55° C. for 30 minutes to obtain an extrusion masterbatch; wherein:

[0103] The polyester masterbatch is a mixture of PET masterbatch and PEN masterbatch, and the mass ratio of PET masterbatch to PEN masterbatch is 3:1.

[0104] Among them, the addition amount of composite reinforced modified particles is 3.2% of the mass of polyester masterbatch;

[0105] Step 2, adding the extrusion masterbatch into the extruder, melting and extruding at 265°C, cooling, and casting at 30°C;

[0106] Step 3, preheating the cast sheet at 70°C, and then longitudinally stretching it at 120°C on a longitudinal stretching machine to obtain a longitudinally stretched sheet, with a longitudinal stretching ratio of 3.5 times;

[0107] Step 4, preheating the longitudinally stretched sheet at 95°C, and then transversely stretching it at 115°C on a transverse stretching machine to obtain a biaxially stretched sheet, with a transverse stretching ratio of 3 times;

[0108] Step 5: The biaxially stretched sheet is subjected to a shaping treatment at 90° C., and finally cooled, rolled up, and trimmed to obtain a high-performance composite capacitor base film.

[0109] In this embodiment, the composite reinforced modified particles are prepared by the following method:

[0110] S1. Preparation of acid-modified carbon nanotubes:

[0111] 5 g of multi-walled carbon nanotubes were added to a mixed solution of 300 mL of 98 wt% concentrated nitric acid and 100 mL of 67 wt% concentrated nitric acid, refluxed at 90° C. for 6 h, cooled, filtered, washed with deionized water until neutral, and vacuum dried at 110° C. for 4 h to obtain acid-modified carbon nanotubes;

[0112] S2. Preparation of modified particle intermediates:

[0113] S2-1, 1.5 g of acid-modified carbon nanotubes, 2 g of nano-SiO2, and 0.852 g of aluminum nitrate were added to a mixed solution consisting of 300 mL of deionized water and 200 mL of ethanol, and ultrasonically dispersed for 30 min;

[0114] S2-2, adding 720 mg of glucose, 332 mg of tert-butylhydroquinone, 184 mg of ethylenediamine, and 690 mg of salicylic acid to the mixture obtained in step S2-1, and ultrasonically dispersing for 45 minutes to obtain a precursor solution;

[0115] S2-3, transferring the precursor solution to a polytetrafluoroethylene-lined reactor, reacting at 185°C for 10 hours, cooling to room temperature after the reaction, filtering, washing the solid with deionized water and ethanol in sequence, and then vacuum drying at 90°C for 12 hours to obtain a modified particle intermediate;

[0116] S3. Take 1 g of the modified particle intermediate and 2 mmol of phenylacetic acid, add them into 50 mL of ethanol, reflux at 58° C. for 16 h, filter, wash the solid product with ethanol, and then dry at 70° C. for 12 h to obtain composite reinforced modified particles.

[0117] Example 2

[0118] A high-performance composite capacitor base film, the preparation method of which comprises the following steps:

[0119] Step 1: Mix the polyester masterbatch and the composite reinforced modified particles at 55° C. for 30 minutes to obtain an extrusion masterbatch; wherein:

[0120] The polyester masterbatch is a mixture of PET masterbatch and PEN masterbatch, and the mass ratio of PET masterbatch to PEN masterbatch is 3:1.3.

[0121] Among them, the addition amount of composite reinforced modified particles is 2.8% of the mass of polyester masterbatch;

[0122] Step 2, adding the extrusion masterbatch into the extruder, melting and extruding at 265°C, cooling, and casting at 30°C;

[0123] Step 3, preheating the cast sheet at 70°C, and then longitudinally stretching it at 120°C on a longitudinal stretching machine to obtain a longitudinally stretched sheet, with a longitudinal stretching ratio of 3.5 times;

[0124] Step 4, preheating the longitudinally stretched sheet at 95°C, and then transversely stretching it at 115°C on a transverse stretching machine to obtain a biaxially stretched sheet, with a transverse stretching ratio of 3 times;

[0125] Step 5: The biaxially stretched sheet is subjected to a shaping treatment at 90° C., and finally cooled, rolled up, and trimmed to obtain a high-performance composite capacitor base film.

[0126] In this embodiment, the composite reinforced modified particles are prepared by the following method:

[0127] S1. Preparation of acid-modified carbon nanotubes:

[0128] 5 g of multi-walled carbon nanotubes were added to a mixed solution of 300 mL of 98 wt% concentrated nitric acid and 100 mL of 67 wt% concentrated nitric acid, refluxed at 90° C. for 6 h, cooled, filtered, washed with deionized water until neutral, and vacuum dried at 110° C. for 4 h to obtain acid-modified carbon nanotubes;

[0129] S2. Preparation of modified particle intermediates:

[0130] S2-1, 1.5 g of acid-modified carbon nanotubes, 2 g of nano-SiO2, and 0.852 g of aluminum nitrate were added to a mixed solution consisting of 300 mL of deionized water and 200 mL of ethanol, and ultrasonically dispersed for 30 min;

[0131] S2-2, adding 720 mg of glucose, 332 mg of tert-butylhydroquinone, 184 mg of ethylenediamine, and 690 mg of salicylic acid to the mixture obtained in step S2-1, and ultrasonically dispersing for 45 minutes to obtain a precursor solution;

[0132] S2-3, transferring the precursor solution to a polytetrafluoroethylene-lined reactor, reacting at 185°C for 10 hours, cooling to room temperature after the reaction, filtering, washing the solid with deionized water and ethanol in sequence, and then vacuum drying at 90°C for 12 hours to obtain a modified particle intermediate;

[0133] S3. Take 1 g of the modified particle intermediate and 2 mmol of phenylacetic acid, add them into 50 mL of ethanol, reflux at 58° C. for 16 h, filter, wash the solid product with ethanol, and then dry at 70° C. for 12 h to obtain composite reinforced modified particles.

[0134] Example 3

[0135] A high-performance composite capacitor base film, the preparation method of which comprises the following steps:

[0136] Step 1: Mix the polyester masterbatch and the composite reinforced modified particles at 55° C. for 30 minutes to obtain an extrusion masterbatch; wherein:

[0137] The polyester masterbatch is a mixture of PET masterbatch and PEN masterbatch, and the mass ratio of PET masterbatch to PEN masterbatch is 3:0.9.

[0138] Among them, the addition amount of composite reinforced modified particles is 3.4% of the mass of polyester masterbatch;

[0139] Step 2, adding the extrusion masterbatch into the extruder, melting and extruding at 265°C, cooling, and casting at 30°C;

[0140] Step 3, preheating the cast sheet at 70°C, and then longitudinally stretching it at 120°C on a longitudinal stretching machine to obtain a longitudinally stretched sheet, with a longitudinal stretching ratio of 3.5 times;

[0141] Step 4, preheating the longitudinally stretched sheet at 95°C, and then transversely stretching it at 115°C on a transverse stretching machine to obtain a biaxially stretched sheet, with a transverse stretching ratio of 3 times;

[0142] Step 5: The biaxially stretched sheet is subjected to a shaping treatment at 90° C., and finally cooled, rolled up, and trimmed to obtain a high-performance composite capacitor base film.

[0143] In this embodiment, the composite reinforced modified particles are prepared by the following method:

[0144] S1. Preparation of acid-modified carbon nanotubes:

[0145] 5 g of multi-walled carbon nanotubes were added to a mixed solution of 300 mL of 98 wt% concentrated nitric acid and 100 mL of 67 wt% concentrated nitric acid, refluxed at 90° C. for 6 h, cooled, filtered, washed with deionized water until neutral, and vacuum dried at 110° C. for 4 h to obtain acid-modified carbon nanotubes;

[0146] S2. Preparation of modified particle intermediates:

[0147] S2-1, 1.5 g of acid-modified carbon nanotubes, 2 g of nano-SiO2, and 0.852 g of aluminum nitrate were added to a mixed solution consisting of 300 mL of deionized water and 200 mL of ethanol, and ultrasonically dispersed for 30 min;

[0148] S2-2, adding 720 mg of glucose, 332 mg of tert-butylhydroquinone, 184 mg of ethylenediamine, and 690 mg of salicylic acid to the mixture obtained in step S2-1, and ultrasonically dispersing for 45 minutes to obtain a precursor solution;

[0149] S2-3, transferring the precursor solution to a polytetrafluoroethylene-lined reactor, reacting at 185°C for 10 hours, cooling to room temperature after the reaction, filtering, washing the solid with deionized water and ethanol in sequence, and then vacuum drying at 90°C for 12 hours to obtain a modified particle intermediate;

[0150] S3. Take 1 g of the modified particle intermediate and 2 mmol of phenylacetic acid, add them into 50 mL of ethanol, reflux at 58° C. for 16 h, filter, wash the solid product with ethanol, and then dry at 70° C. for 12 h to obtain composite reinforced modified particles.

[0151] Comparative Example 1

[0152] This example is basically the same as Example 1, except that the polyester masterbatch is pure PET masterbatch.

[0153] Comparative Example 2

[0154] This example is basically the same as Example 1, except that no composite reinforcing modified particles are added.

[0155] Comparative Example 3

[0156] This example is basically the same as Example 1, except that in this example, the composite reinforced modified particles are prepared by the following method:

[0157] S1, preparing acid-modified carbon nanotubes, the same as in Example 1;

[0158] S2. Preparation of modified particle intermediates:

[0159] S2-1, 1.5 g of acid-modified carbon nanotubes, 2 g of nano-SiO2, and 0.852 g of aluminum nitrate were added to a mixed solution consisting of 300 mL of deionized water and 200 mL of ethanol, and ultrasonically dispersed for 30 min to obtain a precursor solution;

[0160] S2-2, transferring the precursor solution to a polytetrafluoroethylene-lined reactor, reacting at 185°C for 10 hours, cooling to room temperature after the reaction, filtering, washing the solid with deionized water and ethanol in sequence, and then vacuum drying at 90°C for 12 hours to obtain a modified particle intermediate;

[0161] S3. Same as Example 1.

[0162] Comparative Example 4

[0163] This example is basically the same as Example 1, except that in this example, the composite reinforced modified particles are prepared by the following method:

[0164] S1, preparing acid-modified carbon nanotubes, the same as in Example 1;

[0165] S2. Preparation of modified particle intermediates:

[0166] S2-1, take 1.5g of acid-modified carbon nanotubes and 2g of nano-SiO2, add them into a mixed solution consisting of 300mL of deionized water and 200mL of ethanol, and disperse them by ultrasonic for 30min;

[0167] S2-2, adding 720 mg of glucose, 332 mg of tert-butylhydroquinone, 184 mg of ethylenediamine, and 690 mg of salicylic acid to the mixture obtained in step S2-1, and ultrasonically dispersing for 45 minutes to obtain a precursor solution;

[0168] S2-3, transferring the precursor solution to a polytetrafluoroethylene-lined reactor, reacting at 185°C for 10 hours, cooling to room temperature after the reaction, filtering, washing the solid with deionized water and ethanol in sequence, and then vacuum drying at 90°C for 12 hours to obtain a modified particle intermediate;

[0169] S3. Same as Example 1.

[0170] Comparative Example 5

[0171] This example is basically the same as Example 1, except that in this example, the composite reinforced modified particles are prepared by the following method:

[0172] S1. Preparation of modified particle intermediates:

[0173] S1-1, add 2g of nano-SiO2 and 0.852g of aluminum nitrate into a mixed solution consisting of 300mL of deionized water and 200mL of ethanol, and disperse by ultrasonic for 30min;

[0174] S1-2, adding 720 mg of glucose, 332 mg of tert-butylhydroquinone, 184 mg of ethylenediamine, and 690 mg of salicylic acid to the mixture obtained in step S1-1, and ultrasonically dispersing for 45 minutes to obtain a precursor solution;

[0175] S1-3, transferring the precursor solution to a polytetrafluoroethylene-lined reactor, reacting at 185°C for 10 hours, cooling to room temperature after the reaction, filtering, washing the solid with deionized water and ethanol in sequence, and then vacuum drying at 90°C for 12 hours to obtain a modified particle intermediate;

[0176] S3. Same as Example 1.

[0177] The following performance tests were performed on the capacitor base films prepared in Examples 1-3 and Comparative Examples 1-5.

[0178] 1. Antioxidant performance test of composite reinforced modified particles

[0179] The composite reinforced modified particles prepared in Example 1 were prepared into a dispersion with a concentration of 0.5 mg / mL using ethanol, and the total antioxidant capacity detection kit (DPPH method, Isejiu (Jiangsu Lianyungang) Biotechnology Co., Ltd.) was used to detect the antioxidant properties of the dispersion within a certain period of time.

[0180] Determination principle: DPPH is a stable free radical with strong absorption near 515nm; after adding antioxidants, a decolorization reaction will occur, the absorption at 515nm will decrease, and the absorbance at 515nm is proportional to the antioxidant content.

[0181] Reference Figure 1 , are the test results of the antioxidant properties of the composite reinforced modified particles. It can be seen that the composite reinforced modified particles exhibit good antioxidant ability.

[0182] 2. Reference Figure 2 , is the infrared absorption spectrum of the composite enhanced modified particles prepared in Example 1. It can be seen that the surface of the composite enhanced modified particles has abundant carboxyl and hydroxyl groups and a benzene ring structure; 820cm -1 The absorption peaks on the left and right come from the bending vibration of Al-O-Al, 1590 cm -1 The G peaks on the left and right come from multi-walled carbon nanotubes, 1100 and 920 cm -1 The absorption peaks on the left and right come from the silicon-oxygen bond; 1385cm -1 The absorption peaks around 1190cm come from the stretching vibration of the benzene ring. -1 The absorption peaks on the left and right are derived from phenolic hydroxyl groups. Figure 1 The characterization results can illustrate the successful synthesis of composite reinforced modified particles.

[0183] 3. Tensile strength test

[0184] Referring to the standard ASTM D882-12 "Standard Test Method for Tensile Properties of Films and Sheets", a universal tensile testing machine was used to test the tensile breaking strength of the capacitor base films prepared in Examples 1-3 and Comparative Examples 1-5;

[0185] 4. Thermal oxygen aging resistance test

[0186] Heat aging resistance: The capacitor base films prepared in Examples 1-3 and Comparative Examples 1-5 were placed in hot air at 100°C for artificial accelerated aging for 150 hours. After cooling to room temperature, the longitudinal tensile strength was measured again. The heat aging resistance was measured by the retention rate of the longitudinal tensile strength. The larger the value, the better the heat aging resistance.

[0187] 5. Thermal shrinkage test

[0188] The heat shrinkage of the polypropylene capacitor base films prepared in Examples 1-3 and Comparative Examples 1-5 at 150° C. was tested according to ASTM D2732;

[0189] The test results of tensile strength, thermal oxygen aging resistance and thermal shrinkage are shown in Table 1 below:

[0190] Table 1

[0191]

[0192] It can be seen from the test results in Table 1 that the base films prepared in Examples 1-3 have excellent mechanical strength and exhibit good heat-oxidative aging resistance and heat resistance. No PEN masterbatch was added to the polyester masterbatch in Comparative Example 1, resulting in a significant decrease in the overall performance; no composite reinforced modified particles were added in Comparative Example 2, resulting in a decrease in the overall performance of the base film; the results of Comparative Example 3 can illustrate that the carbon dots in the composite reinforced modified particles can improve the excellent antioxidant capacity; in Comparative Example 4, due to the lack of the multiple cross-linking effects of aluminum in the preparation process and the subsequent strengthening effect of aluminum oxide in the base film, the tensile strength, heat resistance, and heat-oxidative aging resistance all decreased; in Comparative Example 5, due to the lack of acid-modified carbon nanotubes, the overall performance also decreased significantly.

[0193] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a high-performance composite capacitor base film, characterized in that: The following steps are involved: Step 1: mixing polyester masterbatch and composite reinforced modified particles to obtain extrusion masterbatch; Wherein, the polyester masterbatch is a mixture of PET masterbatch and PEN masterbatch; Step 2, adding the extrusion masterbatch into the extruder for melting and extrusion, cooling, and casting; Step 3, preheating the cast sheet, and then longitudinally stretching it on a longitudinal stretching machine to obtain a longitudinally stretched sheet; Step 4, preheating the longitudinally stretched sheet, and then performing transverse stretching on a transverse stretching machine to obtain a biaxially stretched sheet; Step 5, shaping the biaxially stretched sheet, and finally cooling, winding, and trimming to obtain the high-performance composite capacitor base film; The composite reinforced modified particles are prepared by the following method: S1, preparing acid-modified carbon nanotubes; S2. Preparation of modified particle intermediates: S2-1, adding acid-modified carbon nanotubes, nano-SiO2, and aluminum nitrate into a mixed solution of deionized water and ethanol, and performing ultrasonic dispersion; S2-2, adding glucose, tert-butylhydroquinone, ethylenediamine and salicylic acid to the mixture obtained in step S2-1, and dispersing by ultrasonication to obtain a precursor solution; S2-3, transferring the precursor solution to a reactor, heating the reaction, cooling to room temperature after the reaction, filtering, washing the solid, and then vacuum drying to obtain a modified particle intermediate; S3, modifying the surface of the modified particle intermediate with phenylacetic acid to obtain the composite enhanced modified particle.

2. The method for preparing a high-performance composite capacitor base film according to claim 1, characterized in that: The following steps are involved: Step 1, mixing the polyester masterbatch and the composite reinforced modified particles at 40-70° C. for 30 minutes to obtain an extrusion masterbatch; The polyester masterbatch is a mixture of PET masterbatch and PEN masterbatch, and the mass ratio of PET masterbatch to PEN masterbatch is 5:1-2.5:1; The addition amount of composite reinforced modified particles is 1.8-4.5% of the mass of polyester masterbatch; Step 2, adding the extrusion masterbatch into the extruder, melting and extruding at 250-270°C, cooling, and casting at 25-35°C; Step 3, preheating the cast sheet at 60-70° C., and then longitudinally stretching it at 70-80° C. on a longitudinal stretching machine to obtain a longitudinally stretched sheet, with a longitudinal stretching ratio of 3-3.5 times; Step 4, preheating the longitudinally stretched sheet at 85-95°C, and then transversely stretching it at 110-125°C on a transverse stretching machine to obtain a biaxially stretched sheet with a transverse stretching ratio of 2.5-3.5 times; Step 5: The biaxially stretched sheet is subjected to a shaping treatment at 75-95° C., and finally cooled, rolled up, and trimmed to obtain the high-performance composite capacitor base film.

3. The method for preparing a high-performance composite capacitor base film according to claim 2, characterized in that: The following steps are involved: Step 1, mixing the polyester masterbatch and the composite reinforced modified particles at 55° C. for 30 minutes to obtain an extrusion masterbatch; in, The polyester masterbatch is a mixture of PET masterbatch and PEN masterbatch, and the addition amount of the composite reinforced modified particles is 3.2% of the mass of the polyester masterbatch; Step 2, adding the extrusion masterbatch into the extruder, melting and extruding at 265°C, cooling, and casting at 30°C; Step 3, preheating the cast sheet at 70° C., and then longitudinally stretching it at 80° C. on a longitudinal stretching machine to obtain a longitudinally stretched sheet, with a longitudinal stretching ratio of 3.5 times; Step 4, preheating the longitudinally stretched sheet at 95°C, and then transversely stretching it at 115°C on a transverse stretching machine to obtain a biaxially stretched sheet with a transverse stretching ratio of 3 times; Step 5: The biaxially stretched sheet is subjected to a shaping treatment at 90° C., and finally cooled, rolled up, and trimmed to obtain the high-performance composite capacitor base film.

4. The method for preparing a high-performance composite capacitor base film according to claim 3, characterized in that: In the polyester masterbatch, the mass ratio of PET masterbatch:PEN masterbatch is 3:

1.

5. The method for preparing a high-performance composite capacitor base film according to claim 1, characterized in that: Step S2 is specifically as follows: S2-1, add 0.75-3g of acid-modified carbon nanotubes, 1-4g of nano-SiO2, and 0.426-1.7g of aluminum nitrate into a mixed solution consisting of 150-600mL of deionized water and 100-400mL of ethanol, and disperse by ultrasonic for 15-60min; S2-2, adding 360-1440 mg of glucose, 166-664 mg of tert-butylhydroquinone, 92-368 mg of ethylenediamine, and 345-1380 mg of salicylic acid to the mixture obtained in step S2-1, and ultrasonically dispersing for 30-90 min to obtain a precursor solution; S2-3. Transfer the precursor solution to a polytetrafluoroethylene-lined reactor, react at 175-200°C for 6-12 hours, cool to room temperature after the reaction, filter, wash the solid with deionized water and ethanol in turn, and then vacuum dry at 80-95°C for 6-24 hours to obtain a modified particle intermediate.

6. The method for preparing a high-performance composite capacitor base film according to claim 1, characterized in that: Step S3 is specifically as follows: 0.5-2 g of the modified particle intermediate and 1-4 mmol of phenylacetic acid are added to 25-100 mL of ethanol, refluxed at 50-65° C. for 8-24 h, filtered, the solid product is washed with ethanol, and then dried at 60-80° C. for 6-20 h to obtain the composite reinforced modified particles.

7. The method for preparing a high-performance composite capacitor base film according to claim 1, characterized in that: The composite reinforced modified particles are prepared by the following method: S2. Preparation of modified particle intermediates: S2-1, 1.5 g of acid-modified carbon nanotubes, 2 g of nano-SiO2, and 0.852 g of aluminum nitrate were added to a mixed solution consisting of 300 mL of deionized water and 200 mL of ethanol, and ultrasonically dispersed for 30 min; S2-2, adding 720 mg of glucose, 332 mg of tert-butylhydroquinone, 184 mg of ethylenediamine, and 690 mg of salicylic acid to the mixture obtained in step S2-1, and ultrasonically dispersing for 45 minutes to obtain a precursor solution; S2-3, transferring the precursor solution to a polytetrafluoroethylene-lined reactor, reacting at 185°C for 10 hours, cooling to room temperature after the reaction, filtering, washing the solid with deionized water and ethanol in sequence, and then vacuum drying at 90°C for 12 hours to obtain a modified particle intermediate; S3, taking 1 g of the modified particle intermediate and 2 mmol of phenylacetic acid, adding them into 50 mL of ethanol, refluxing at 58° C. for 16 h, filtering, washing the solid product with ethanol, and then drying at 70° C. for 12 h to obtain the composite reinforced modified particles.

8. A high-performance composite capacitor base film, characterized in that: It is prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Multilayer composite BOPE capacitor film and its preparation method

    CN114103348B

  • High-performance PET base film and preparation method thereof

    CN114410071A

  • Back sheet for solar cell with high heat dissipation and high insulation

    KR101505746B1